Uma análise histórica do conceito de comportamento governado por regra na obra de B. F. Skinner - Malavazzi, Dante Marino (2014)
Inspired by the debate over the definitions and functions of rules in the control of human behavior, the present study aimed to analyze the historical development of the concept of rule-governed behavior in B. F. Skinner s work. As justification for this work, I considered their possible contributions to non-experimental production in behavior analysis, to the conceptual clarification of discipline, and to intervention in complex phenomena. In order to identify Skinner s publications on rule-governed behavior, I analyzed the collection of the Laboratory of Historical Studies in Behavior Analysis (PUC-SP), texts of the author s interlocutors, and Index of 17 works by Skinner. Together, these strategies allowed the identification of 65 publications of the author on the subject, whose reading in chronological order resulted in six categories of analysis: (a) Definition of Rule, (b) Types of Rule, (c) Functions of Rule, (d) Formulation of Rule, (e) Rule Following, and (f) Rule-Governed Behavior versus Contingency-Shaped Behavior. Among the results, although it is possible to identify in Skinner s work different stimulus functions assigned to descriptions of contingencies, the author admits the existence of rules without including their possible functions in the control of human behavior. This study also clarifies the criteria by which Skinner characterizes different types of rule in his bibliographical production, presents the author s explanations for the formulation and following of rules, and organizes the differences pointed out by Skinner between rule-governed behavior and contingency-shaped behavior